Penerapan Terapi Eksistensial Humanistik Dalam Mengatasi Hopelessness (Studi Kasus Klien “W”) - Rara Regita Niosa; Kusnadi Kusnadi; Neni Noviza (Journal of Society Counseling, 2023)
This research examines about. "The Application of Humanistic Existential Therapy in Overcoming Hopelessness (Case Study of Client "W" in Class 1 LPKA Palembang)". This study aims to find out first, the description of hopelessness in client "W" in LPKA class 1 Palembang and second, the application of humanistic existential therapy in overcoming hopelessness in client "W" in LPKA class 1 Palembang. The research used a qualitative field research approach and a case study method. Data collection tools in this study are observation, interviews and communication. Data analysis techniques in this study are pattern matching, explanation and time series analysis. The subjects of this study were clients "W", friends of clients "W" and prison officers. The description of hopelessness experienced by client "W" is seen from 4 aspects, namely: aspects of rejection, destruction, aggression and termination. In the rejection aspect, client "W" experiences a condition of refusing or denying having a hand in every problem, looking for scapegoats to blame or being the cause of problems in his life and always seeking justification for what he is doing and avoiding responsibility. In the aspect of destruction, client "W" experiences a condition of seeing himself as no better than others, committing acts that harm himself both physically and non-physically, believing himself to be no better than others and saying things that weaken or demean himself either intentionally or unintentionally. In the aggression aspect, client "W" experiences a condition where he begins to hurt others, whether intentional or not, performs actions that harm/endanger other people, hurts other people's feelings both verbally and verbally and says harsh words that offend other people's feelings. In the termination aspect, client "W" experiences a state of mind to kill himself, aka suicide, while the application of humanistic existential therapy to client "W" goes according to the stages of existential humanistic therapy at the initial stage in the counseling process, namely collecting client data first. in order to facilitate the counseling process after that in the second stage of humanistic existential therapy focusing on the implementation of counseling focusing on current behavior, the counselor seeks out and asks the client about the problems that occur next at the evaluation stage where in this stage the counselee re-evaluates the activities that have been carried out in the first and second stages are to find out what may not have been discussed or followed up on the causes or problems faced by the client so that when the counseling process ends the problems that occur can gradually disappear and the last is the fourth stage in humanistic existential therapy in this stage the counseling concludes again the problem of hopelessness which is overcome by existential humanistic therapy and the results of the application of the first humanistic existential therapy, namely in the aspect of rejection the client "W" has started to be able to overcome his own problems, solve problems well and be more responsible, the second is in the aspect of client destruction " W "has started to open his mind, is more confident and can overcome the problems that occur, the third in the aggression aspect the client "W" is more careful in acting both verbally and non-verbally, is more restrained and solves problems in a good and the fourth is the aspect of termination of the client "W" who thinks more positively and gets closer to Allah SWT. Keywords: Humanistic Existential Therapy, Hopelessness